86.2k views
2 votes
-K2 – (4k - 6n) + 9n; k = - 1 and n= - 4

For k= - 1 and n= -4, -K2 - (4k - 6n) + 9n =
(Simplify your answer.)

User Kim Larsen
by
4.7k points

2 Answers

4 votes

Answer:

-18

)())()()()()()()( ;)

User Rajesh Patel
by
4.9k points
3 votes

Answer:

The simplified answer of the given equation is -57.

Explanation:

For this problem, we are given values for our variables.

k = -1

n = -4

So, let's plug these numbers into our expression so we can easily solve it.

-(-1)² - (4(-1) - 6(-4)) + 9(-4)

Simplify your parentheses.

-(-1)² - (-4 + 24) - 36

-(-1)² - 20 - 36

Now, simplify your exponents.

-1 - 20 - 36

Combine -1 and -20.

-21 - 36

Now, subtract -21 from 36.

-57

User Luiscrjr
by
4.5k points